The Role of Modeling in Motor Skill Learning - Zetou Ελένη; Vernadakis Νικόλαος; Tzetzis Γιώργος; Kioumourtzoglou Ευθύµης (Inquiries in Physical Education and Sport, 2003)
Motor skills are the most common types of knowledge that individuals must acquire over the life span. Observational learning is one of the primary and effective way in which individuals acquire new knowledge and skills. Observational learning of a motor skill involves: a) observation of a model, which allows someone to understand and imitate a modeled demonstration, and b) self-observation, which allows someone to actively regulate one’s own learning and performance of a motor skill. This paper reviews the theoretical explanations and the factors that influence modeling: a) the model characteristics, b) the type of task, c) the observer characteristic, and d) the strategies of practice which accompany the demonstration. So, if teachers and coaches could learn the factors that influence the effectiveness of modeling, could use modeling to teaching and practice, in order to have primary results to motor skill learning